Housing for all in India - de la Maisonneuve, Christine (OECD Economics Department Working Papers, 2020)
Housing is key for well-being and for spatial and social mobility. In India, the housing market is characterised by excess demand for affordable dwellings, a small rental market and an oversupply of high-end housing, especially in urban areas